Review - Fernandes, Pedro (2023)
The use of the QR code application as a pedagogical resource in the teaching and learning process Ribas, A.C., Oliveira, B.S., Gubaua, C.A., Reis, G.D.R., & Contreras, H.S.H. (2017). The use of the QR code application as a pedagogical resource in the teaching and learning process. Pedagogical Essays, 7(2), 12-21. From the moment a new tool or technological application is born, studies are quickly initiated that discuss its use, or attempted use, in pedagogical contexts, such is the importance that the teaching-learning process plays in our lives. The article under analysis, which reading is recommended, was published in the journal Ensaios Pedagógicos in December 2017, relying on the experience of several authors linked to teaching: Ana Carolina Ribas, Bianca Soares Oliveira, Camila Aparecida Gubaua, Gisele da Rocha Reis and Humberto Silvano Herrera Contreras.